Post-Partum Depression: Diagnosis, Screening, and Treatment - Suzanna Freerksen; W. Brooks; Sarah Siddiqui (Association of American Medical Colleges, 2015)
Abstract This is a team-based learning (TBL) module aimed to help medical students identify and treat post-partum depression (PPD). In the 10-item individual readiness assessment test (IRAT) and group readiness assessment test (GRAT), we look at the epidemiology of PPD, talk about screening, and start thinking about differential diagnosis. Most of the questions are taken directly from the suggested reading since our TBL's IRAT and GRAT were part of the students' clerkship grade. However, the questions are also targeted to dispel several myths about postpartum depression. If the readiness assurance test is used without the suggested reading, more time should be allotted to the IRAT and GRAT portions of the module as there will be a more lively discussion. In the clinical application exercise, we look at a screening instrument for PPD that we learned about earlier in the module in the readiness assurance test. We then delve into the differential diagnosis of PPD, as well as discuss the basics of treatment. This is done by meeting a case study patient, Cassandra. First in the small groups and then as a large group, we discuss Cassandra's differential diagnosis, namely ruling out the baby blues, substance abuse, and medical issues that could be causing the mood changes. Dosages of medications are not discussed in the facilitator's guide, but the basics of prescribing and nonpharmacological methods of treatment are discussed. We have found that the subject matter is intriguing enough that the discussion on the topic often continues into the hallway. This TBL module is targeted at medical students in their obstetrics/gynecology clerkship or in their psychiatry clerkship. The authors are psychiatrists, but the module was classroom tested several times in an obstetrics/gynecology clerkship and, due to the positive response from medical students, may be implemented in our psychiatry clerkship. The group size ranged from 10 to 14 learners. The TBL module has evolved through feedback from the learners. For example, more emphasis was placed on a wider differential diagnosis after feedback when we identified this need during implementation.